2007
DOI: 10.1002/mrd.20624
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sperm forward motility‐related proteins in human seminal plasma

Abstract: Seminal plasma, an amorphous material that exists in semen, contains proteins related to sperm forward motility. Employing affinity chromatography with ConA beads and protein ultrafiltration, we isolated and concentrated proteins from heated human seminal plasma. Results of computer-assisted semen analyses (CASA) demonstrated that the forward motility index of bovine spermatozoa from the epididymal caput, incubated with proteins and theophylline, was significantly different from that of spermatozoa incubated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 48 publications
4
27
0
4
Order By: Relevance
“…In a previous study, we reported that ZAG was primarily related to sperm forward motility in human semen (Ding et al 2007). Our data supported the fact that ZAG in human seminal plasma might be integrated with a-1-antitrypsin (AAT) and was capable of initiating forward motility in immature immotile spermatozoa.…”
Section: Introductionsupporting
confidence: 86%
“…In a previous study, we reported that ZAG was primarily related to sperm forward motility in human semen (Ding et al 2007). Our data supported the fact that ZAG in human seminal plasma might be integrated with a-1-antitrypsin (AAT) and was capable of initiating forward motility in immature immotile spermatozoa.…”
Section: Introductionsupporting
confidence: 86%
“…Moreover, our endpoint in this study was seminal alteration per se, which makes it necessary to perform a confirmatory prospective multicentric cohort study in order to validate our findings, as well as to better define cutoff values. Finally, it is important to better understand the role of seminal plasma proteins in different causes of infertility, because this is a promising field that can indicate potential biomarkers, and because the regulatory activity of extracellular proteins in seminal plasma is fundamental for proper sperm function after ejaculation [48].…”
Section: Discussionmentioning
confidence: 99%
“…The seminal plasma ZAG is synthesized by prostate epithelial cells and secreted into seminal fluid (62), and it constitutes 30% of the proteins present in the seminal fluid (18). Hale et al (44) determined the expression of ZAG in prostate tumors and found that ZAG is produced by 73% of prostate cancers.…”
Section: Zag and Cancermentioning
confidence: 99%
“…The mechanisms by which cAMP activates sperm cytosolic cAMP, which in turn phosphorylates multiple intrasperm phosphoproteins that may regulate flagellar motility (112,113) of spermatozoa. Moreover, ZAG is also a protein that is directly related to sperm motility and in turn fertilization (62).…”
Section: Fertilizationmentioning
confidence: 99%